Ethical preferences for influencing superiors: A 41-society study - Ralston, David A; Egri, Carolyn P; de la Garza Carranza, María Teresa; Ramburuth, Prem; Terpstra-Tong, Jane; Pekerti, Andre A; Girson, Ilya; Herrig, Harald; Dabic, Marina; Tang, Moureen; Wan, Paulina; Hallinger, Philip; et al. (Journal of International Business Studies, 2009)
With a 41-society sample of 9990 managers and professionals, we used hierarchical linear modeling to investigate the impact of both macro-level and micro-level predictors on subordinate influence ethics. While we found that both macro-level and micro-level predictors contributed to the model definition, we also found global agreement for a subordinate influence ethics hierarchy. Thus our findings provide evidence that developing a global model of subordinate ethics is possible, and should be based upon multiple criteria and multilevel variables.